Experimental parameterisation of principal physics in buoyancy variations of marine teleost eggs - Jung, Kyung Mi; Folkvord, Arild; Kjesbu, Olav Sigurd; Sundby, Svein (PLoS ONE, 2015)
It is generally accepted that the high buoyancy of pelagic marine eggs is due to substantial influx of water across the cell membrane just before ovulation. Here we further develop the theoretical basis by applying laboratory observations of the various components of the fertilized egg in first-principle equations for egg specific gravity (ρegg) followed by statistical validation. We selected Atlantic cod as a model animal due to the affluent amount of literature on this species, but also undertook additional dedicated experimental works. We found that specific gravity of yolk plus embryo is central in influencing ρegg and thereby the buoyancy. However, our established framework documents the effect on ρegg of the initial deposition of the heavy chorion material in the gonad prior to spawning. Thereafter, we describe the temporal changes in ρegg during incubation: Generally, the eggs showed a slight rise in ρegg from fertilization to mid-gastrulation followed by a gradual decrease until full development of main embryonic organs just before hatching. Ontogenetic changes in ρegg were significantly associated with volume and mass changes of yolk plus embryo. The initial ρegg at fertilization appeared significantly influenced by the chorion volume fraction which is determined by the combination of the final chorion volume of the oocyte and of the degree of swelling (hydrolyzation) prior to spawning. The outlined principles and algorithms are universal in nature and should therefore be applicable to fish eggs in general. publishedVersion